Outcomes After Multimodality Treatment of Pancreatic Cancer in an Unselected Single-Center Cohort - Heervä E; Väliaho V; Nurmi H; Lietzen E; Ålgars A; Kauhanen S (Cancer Management and Research, 2024)
Eetu Heervä,1 Vesa Väliaho,1 Heidi Nurmi,1 Elina Lietzen,2 Annika Ålgars,1 Saila Kauhanen2 1Department of Oncology, Turku University Hospital and University of Turku, Turku, Finland; 2Department of Digestive Surgery, Turku University Hospital and University of Turku, Turku, FinlandCorrespondence: Eetu Heervä, Department of Oncology, Turku University Hospital, Hämeentie 11, Turku, 20521, Finland, Tel +35823130000, Fax +35823131316, Email eetu.heerva@utu.fiBackground: Pancreatic ductal adenocarcinoma (PDAC) remains a lethal and rarely resectable malignancy. Here we explore the outcomes of surgery, as compared to definitive radiotherapy (dRT) or systemic therapy only in PDAC.Methods: Pancreatic surgery and radiotherapy in Southwest Finland have been centralized to Turku University Hospital. Previously validated population-based electronic health records database was searched for all unselected PDAC patients from the years 2009– 2019. Main outcome was median overall survival (mOS). Demographics, pathology, surgery, and oncological treatment data were collected.Results: We identified 1006 patients with PDAC, 49% male, median age 71 years and 77% presenting with metastatic disease. In total, 405 patients were treated; 92 resected, 26 dRT without resection and 287 systemic therapy only. mOS was 34.6 months for resected, 26.7 months for dRT, and 7.5 months for systemic therapy patients. Among the 88 patients with locally advanced inoperable PDAC, dRT was independently associated with longer mOS (26.7 months) as compared to systemic therapy only (mOS 10.6 months). Among the 287 patients treated with systemic therapy only, combination chemotherapy was independently associated with longer mOS (11.6 months) as compared to gemcitabine-monotherapy (6.8 months). In patients progressing to second-line systemic treatment after gemcitabine failure, mOS was the same (5.0 months) with single or combination regimens.Conclusion: Surgery remains the only curative approach for PDAC. In locally advanced PDAC, dRT was associated with longer survival as compared to systemic therapy only. Concerning first-line systemic therapy, our results support the use of combination chemotherapy over single-agent therapy.Keywords: pancreatic cancer, pancreas, pancreatectomy, nab-paclitaxel, chemoradiotherapy